CARE: Combination of Acetylcysteine and Acebrophylline in Moderate to Severe Asthma and COPD Patients - Dhar R; Chawla RK; Rahaman M; Chawla AK; Chaudhary G; Gautam A; Singal R (Journal of Asthma and Allergy)
Raja Dhar,1 Rakesh K Chawla,2 Moumita Rahaman,1 Aditya K Chawla,2 Gaurav Chaudhary,2 Ashutosh Gautam,3 Rajat Singal3 1Department of Pulmonology, Birla Hospital, Kolkata, India; 2Department of Respiratory Medicine, Critical Care, Sleep Medicine Interventional Pulmonology, Chawla Clinic, New Delhi, India; 3Mankind Pharma Ltd, Okhla Phase III, New Delhi, IndiaCorrespondence: Raja Dhar, Department of Pulmonology, Birla Hospital, Kolkata, 700 012, India, Email docaardee@yahoo.comObjective: To assess the efficacy and safety of the combination of N-acetylcysteine and acebrophylline (Combination named Abiways), in patients with moderate to severe COPD and Asthma.Materials and Methods: In this non-randomized, interventional, prospective, single-arm, post-marketing surveillance study, participants were administered Abiways as an add-on therapy for 90 days. The primary endpoint was Quality of Life, evaluated using the COPD Assessment Test (CAT) and Asthma Control Test (ACT) questionnaires. Secondary endpoints included mean FEV1 and FVC changes. Adverse events were recorded throughout the study.Results: 97 (of 102 subjects enrolled) completed the study (76 COPD and 21 Asthma patients, respectively; mean age 57.9 ± 8.1 years; 33 females, 64 males). Overall, FEV1 improved significantly from 1.287L to 1.484L (p < 0.001) with similar statistical improvements in COPD (1.237 L to 1.414 L; p = 001) and asthma (1.477 L to 1.747 L; p = 0.004) subpopulations. COPD patients showed statistically significant improvements in CAT scores (17.2 ± 1.0 to 10.6 ± 0.9, p = 0.0001); however, such significance was not observed in the ACT scores for asthma patients. FVC remained unchanged in all subgroups. No severe adverse events were reported.Conclusion: The combination of N-acetylcysteine and acebrophylline improves QoL in moderate to severe COPD patients and FEV1 in both COPD and asthma patients with a favorable safety and tolerability profile. The combination appears safe and effective for managing obstructive airway disease.Keywords: COPD, asthma, N-acetylcysteine, acebrophylline, CAT score, FEV1, Abiways